ANALISIS KOMPONEN FUNDAMENTAL SISTEM INFORMASI KESEHATAN DAN DAMPAKNYA TERHADAP KUALITAS PELAYANAN - Despitasary (LPPM Universitas Awal Bros, 2025)
This study aims to analyze the fundamental components of Health Information Systems (HIS) and its impact on service quality. It is hoped that the results of this study can provide a deeper understanding of the key components of the HIS and their influence on the quality of health services, as well as develop appropriate strategies for the development and implementation of a more effective HIS.. The methodology used in this research is a literature review, which is based on a review of various articles and scholarly journals from both national and international sources obtained from platforms such as Google Scholar, PubMed, Science Direct, DOAJ, and Garuda. The selection criteria include articles or journals published between 2019 and 2024, related to the fundamental components of health information systems and their impact on service quality. Keywords such as